2022
DOI: 10.1111/jvim.16473
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the origin of atrial tachycardia by 3D electro‐anatomical mapping and treatment by radiofrequency catheter ablation in horses

Abstract: Background: Atrial tachycardia (AT) can be treated by medical or electrical cardioversion but the recurrence rate is high. Three-dimensional electro-anatomical mapping, recently described in horses, might be used to map AT to identify a focal source or reentry mechanism and to guide treatment by radiofrequency ablation.Objectives: To describe the feasibility of 3D electro-anatomical mapping and radiofrequency catheter ablation to characterize and treat sustained AT in horses.Animals: Nine horses with sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…29 , 30 It has a high success rate of almost 100% and a low complication rate. 29 , 30 , 33 , 36 In horses, RFCA has been used successfully for the treatment of atrial tachycardia, 37 but so far not for an AP. The principle of mapping anterograde conducting pathways is to find the earliest ventricular activation site or AP potential.…”
Section: Discussionmentioning
confidence: 99%
“…29 , 30 It has a high success rate of almost 100% and a low complication rate. 29 , 30 , 33 , 36 In horses, RFCA has been used successfully for the treatment of atrial tachycardia, 37 but so far not for an AP. The principle of mapping anterograde conducting pathways is to find the earliest ventricular activation site or AP potential.…”
Section: Discussionmentioning
confidence: 99%
“…In human medicine, radiofrequency ablation would have been used to treat the underlying cause of the AF. Although this technology has not yet been fully developed in horses, the treatment of other arrhythmias, such as sustained atrial tachycardia and an accessory pathway, has been reported (Buschmann et al, 2023; Phillips et al, 2022; Van Steenkiste et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In this horse, recurrence was initiated by an episode of atrial tachycardia. When atrial tachycardia is confirmed as the underlying trigger for developing AF, treatment by 3D electro‐anatomical mapping and radiofrequency catheter ablation could be a successful treatment strategy (Van Steenkiste et al, 2022).…”
Section: Research Tool or Diagnostic Technique?mentioning
confidence: 99%